A frequency estimation method for two adjacent frequencies - Li, Rui; Xuan, Jianping; Shi, Tielin (Measurement : journal of the International Measurement Confederation, 2020)
•Rather than based on the main lobe, the proposed method based on the first side-lobes.•The proposed method suitable for the estimation of two closely adjacent two frequencies.•When the distance of two frequencies is bigger than 1.5 bins, the maximum estimation error is 0.07 bins. The frequency-domain estimation methods are estimate frequency from main-lobe. One shortcoming of these methods lies in the fact that they are not suited to two adjacent frequency components. When the distance between two frequency components is less than 3 DFT bins, former methods are subject to severe spectral interference, which results in considerable errors of estimate. In this paper, a discovery is made that side-lobes have relatively smaller spectral interference as compared to main-lobe, for which a novel estimation method based on the first side-lobes is proposed. As demonstrated by simulation, the proposed method performs better in two adjacent frequency components estimation. When the distance between two frequency components reaches 1.5 bins, the maximum estimation error is approximately 0.07 bins for the two frequencies.